1997
DOI: 10.1016/s0006-3495(97)78662-4
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of neuropeptide Y-[18–36] analogs in hydrophobic environments

Abstract: The interactive and conformational behavior of a series of neuropeptide Y-[18-36] (NPY-[18-36]) analogs in hydrophobic environments have been investigated using reversed-phase high-performance liquid chromatography (RP-HPLC) and circular dichroism (CD) spectroscopy. The peptides studied comprised a series of 16 analogs of NPY-[18-36], each containing a single D-amino acid substitution. The influence of these single L-->D substitutions on the alpha-helical conformation of the NPY-[18-36] analogs in different so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 21 publications
(16 reference statements)
0
20
0
Order By: Relevance
“…First, the relationship between the hydrophobicity of peptides and their inhibition activities was considered in peptide design because a number of studies have reported that the hypocholesterolemic effect of a peptide correlates to increased hydrophobicity 31. RP–HPLC can be especially useful as a physicochemical model of biological systems because its hydrophobic environment may reasonably mimic the hydrophobic environment created, internally, by a protein 32, 33. The overall experimental peptide hydrophobicity, assessed by retention time on RP–HPLC, was compared with peptide inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…First, the relationship between the hydrophobicity of peptides and their inhibition activities was considered in peptide design because a number of studies have reported that the hypocholesterolemic effect of a peptide correlates to increased hydrophobicity 31. RP–HPLC can be especially useful as a physicochemical model of biological systems because its hydrophobic environment may reasonably mimic the hydrophobic environment created, internally, by a protein 32, 33. The overall experimental peptide hydrophobicity, assessed by retention time on RP–HPLC, was compared with peptide inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrophobic lipid‐like surfaces used in RP‐HPLC have become widely used in the study of the surface‐based induction and stabilization of a range of peptides and proteins including amphipathic monomeric α‐helices, dimeric coiled coils and β‐sheet peptides (25–31). In addition, these studies have allowed quantitative analysis of the binding of these peptides to hydrophobic n ‐alkyl chains in terms of partition/hydrophobicity coefficients and stability constants, together with the thermodynamics and kinetics associated with the conformational changes which occur upon binding to hydrophobic surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Under conditions where the hydrophobic interactions are the dominant interactive force between the solutes and the immobilized ligands, a linear dependency of solute retention, log k′ , on the solvent mole fraction, ϕ , required to elute the solute from the surface can be obtained according to log k′ = log k 0 − Sϕ where the log k 0 value is the extrapolated log k′ in the absence of organic solvent ( ϕ = 0) and S is the slope of the plot of log k′ vs. ϕ over a defined k′ range. As shown in various studies (25–31), the variation in the binding properties of peptides as a consequence of conformational effects are reflected in changes in log k′ which provides a sensitive parameter to probe the conformational status of peptides during the interaction with the immobilized lipids. In addition, variation of the temperature allows further information to be gained on the effect of peptide conformation and lipid mobility on membrane interactions.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, it has been shown by several studies that the log U value is a physical parameter which is highly sensitive to the conformational status of the peptide or protein upon interaction with hydrophobic surfaces [11][12][13][14][15][16]. Peptides and proteins interact with hydrophobic surfaces in an orientation-specific manner via a specific hydrophobic contact area.…”
Section: Dependence Of Binding Affinity On Organic Solventmentioning
confidence: 99%